2019
DOI: 10.1080/17430437.2019.1669325
|View full text |Cite
|
Sign up to set email alerts
|

Identity tensions in dual career: the discursive construction of future selves by female Finnish judo athletes

Abstract: Identity tensions in dual career: The discursive construction of future selves by female Finnish judo athletesTo date, few studies have explored how changes in the practices, policies, and politics of sport and education may be implicated in how young athletes think about and plan for the future. Drawing on cultural praxis and feminist poststructuralist frameworks, this paper explores whether and how dual career (DC) policies and practices in Finland guide female judo athletes' imaginings about their future. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Only two studies emphasize the importance of motivation in judo athletes. Coach autonomy support has a major role in self-determined motivation of young judokas [ 33 ]. Silva et al [ 32 ] assessed the profile of mental toughness in judo.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only two studies emphasize the importance of motivation in judo athletes. Coach autonomy support has a major role in self-determined motivation of young judokas [ 33 ]. Silva et al [ 32 ] assessed the profile of mental toughness in judo.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, mental toughness has been responsible for increasing perfectionistic strivings and decreasing perfectionistic concerns in judo and other sports [ 30 , 62 ]. Finally, the concept of a dual career can be a problem for female judo athletes [ 33 ]. Skrubbeltrang et al [ 63 ] demonstrated that the overlap between school and sports in students with higher socioeconomic statuses probably leads them to focus more on learning.…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the fact that female athletes often experience cultural and societal pressure to excel in multiple roles simultaneously and are therefore more likely to invest in DC goals and identities compared to males (Ryba et al, 2021). Indeed, earlier studies have suggested that this pressure may be linked to the beliefs of how female athletes are inferior to male athletes and how pursuing a professional athletic career is not a real career option for them (Kavoura & Ryba, 2020); Ryba et al, 2021: female athletes have been found to feel less competent than male athletes in sport (Ronkainen et al, 2020), are less likely to aim for a professional athletic career (e.g., Kavoura & Ryba, 2020), and are at higher risk of dropping out of sports compared to males (Skrubbeltrang, 2019). Due to the structural inequalities that limit female athletes' access to develop professional athletic careers, they also have a higher need to engage in DC goals compared to males.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that female athletes often experience cultural pressure to invest in educational and DC goals and to excel in multiple roles simultaneously, whereas male athletes have been found to be more relaxed about their career aspiration (Kavoura & Ryba, 2020). Recent scholarship indicates that we may even be witnessing a femininization of DCs; that is, the DC discourses and practices are gendered, and seem to be particularly important for young female athletes (Skrubbeltrang, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This can complement the judo training. The dual career KPI most influenced motivation (9.8%), and thus, it is important to define a coherent plan that avoids conflicts of identity but does not interfere with the judoka's results (Kavoura and Ryba, 2020 ).…”
Section: Discussionmentioning
confidence: 99%